Prevalence of Hearing Loss in Patients with Acute Otitis Media (Journal of Science and Technology, 2016)
The study was a prospective, cross-sectional type conducted at the Ear, Nose and Throat Department of Komfo Anokye Teaching Hospital (KATH) over a six month period from 1st August 2005 to 31st January 2006. Fifty one patients involving 69 ears (few with bilateral and majority with unilateral hearing loss) were interviewed followed by otoscopic ear examination, pure tone audiometry using AC 30 audiometer and tympanometric test. The hearing loss of participants was thus determined before and after treatment to establish the change in hearing over the period. The results showed that hearing loss occurs in majority of sufferers of acute otitis media. The prevalence of acute otitis media (AOM) is low in adults, but it is quite high in children (91.3%) of reported cases.